2015
DOI: 10.1007/s10661-014-4191-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination, sources, and pollution assessment of surface water in the Tianshan Mountains of China

Abstract: In order to gain insight into heavy metal contamination occurring in the surface water of the Tianshan Mountains in northwest China, we collected surface water samples from there, tested heavy metals Pb, Ni, Cd, Co, Hg, As, Cu, Mn, Zn, and Cr, and then we analyzed the data using typical analysis, multivariate statistical, and pollution index methods. Results showed that (1) the order of the average values of the ten kinds of heavy metals in all the water samples was as follows: Zn > Mn > Cu > Co > Ni > Pb > Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…Many studies have shown that Tian-Shan is one of the mountain ranges in central Asia with the largest anthropogenic sources of heavy metals [4][5][6][7][8]. Pb, Cd and Cu concentrations from the Inilchek ice core (central Tian-Shan) reflect declines during the 1980s concurrent with Soviet economic declines, however, due to the rapid industrial and agricultural growth of western China, Pb, Cd and Cu trends increased during the 1990s [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that Tian-Shan is one of the mountain ranges in central Asia with the largest anthropogenic sources of heavy metals [4][5][6][7][8]. Pb, Cd and Cu concentrations from the Inilchek ice core (central Tian-Shan) reflect declines during the 1980s concurrent with Soviet economic declines, however, due to the rapid industrial and agricultural growth of western China, Pb, Cd and Cu trends increased during the 1990s [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mountains are amongst the most fragile environments in the world [3]. Many studies have shown that Tian-Shan is one of the mountain ranges in central Asia with the largest anthropogenic sources of heavy metals [4][5][6][7][8]. Pb, Cd and Cu concentrations from the Inilchek ice core (central Tian-Shan) reflect declines during the 1980s concurrent with Soviet economic declines, however, due to the rapid industrial and agricultural growth of western China, Pb, Cd and Cu trends increase during the 1990s [4].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are many studies regarding with heavy metal concentration in surface waters worldwide (Ma et al, 2015;Zhaoyong et al, 2015;O'Neill et al, 2015;Dević et al, 2016), concentration of heavy metals in a surface water depends upon factors specific to that surface water like substrate sediment concentration, water chemistry, self-purification capacity of river system and anthropogenic activities taking place in the area (Förstner and Prosi, 2013;Islam et al, 2015). Therefore, monitoring and evaluating heavy metal concentrations in water bodies is a case-specific issue.…”
Section: Introductionmentioning
confidence: 99%